Wetting Properties of Simulated and Commercial Contaminants on High Transmittance Superhydrophobic Coating - Michele Ferrari; Francesca Cirisano (Nanomaterials, 2023)
The large and necessary diffusion of huge solar plants in extra urban areas implies the adoption of maintenance strategies especially where human intervention would require high costs and logistic problems. Animal dejections like bird droppings and agricultural sprays are environmental agents able to significantly decrease light absorption and, in some cases, cause serious damage to the electric conversion systems in a photovoltaic panel. In this work, the performance of a superhydrophobic (SH) coating in terms of durable self-cleaning properties and transparency has been studied in the presence of commercial and simulated contaminants on glass reference and solar panel surfaces. Wettability studies have been carried out both in static and dynamic conditions in order to compare the compositional effect of commercial liquids used as fertilizers or pesticides and molecules like pancreatin as model substances simulating bird droppings. From these studies, it can be observed that the superhydrophobic coating, independently from the surface where it is applied, is able to repel water and substances used such as fertilizers or pesticides and substances simulating bird droppings, maintaining its properties and transparency. This kind of approach can provide information to design suitable spray formulations without the above-mentioned drawbacks to be used in natural environment areas and agrosolar plants.